Lack of Correlation between Plasma Neuropeptide Y and Typical and Atypical Febrile Seizures - Hamid Reza Sarokhani; Mohsen Nazari; Parviz Ayazi; Abolfazl Mahyar; Mohammad Mahdi Daneshi-Kohan; Amir Javadi (Acta Medica Iranica, 2013)
It is known that neuropeptide Y which is widely distributed throughout the central nervous system is able to prevent seizures in animals. There are limited studies about the role of neuropeptide Y in febrile seizures. This study was conducted to evaluate the association between plasma neuropeptide Y level and febrile seizures in children. Seventy six patients with typical and atypical febrile seizures (each group 38 patients) and 38 sex and age matched control subjects were enrolled. The mean plasma levels of neuropeptide Y in typical and atypical febrile seizures were 90.60±28.01 and 97.34±41.27 pmol/l respectively. This value in control group was 88.94±32.66 pmol/l. There was no significant differences between groups regarding plasma neuropeptide Y level (P=0.532). Also, there was no significant difference in comparison with case groups (P=0.40). This study revealed that there is no association between plasma neuropeptide Y and febrile seizures.